Does Firm Size, Leverage and Profitability Effect On Coefficient Earnings Response (ERC) with Islamic Social Reporting (ISR) As Intervening Variable ? - Purnama Putra (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the direct and indirect effect of Firm Size, Leverage, and Profitability on Earning Response Coefficient (ERC) with Islamic Social Reporting (ISR) as an intervening variable in manufacturing companies listed in the Indonesian Sharia Stock Index (ISSI) for the period 2014 -2017. The data used are the financial statements of manufacturing companies listed in the Indonesian Sharia Stock Index. Data analysis using multiple linear regression. The sample in this study were 30 manufacturing companies in various business fields, which provided quarterly financial reports. Samples were taken using purposive sampling technique. The results of this study show that partially Firm Size and Profitability have a positive and significant effect on Islamic Social Reporting, while Leverage has no and no significant effect on Islamic Social Reporting. Partially Firm Size and Islamic Social Reporting have no and insignificant effect on the Earning Response Coefficient, but Leverage has a negative and significant effect while Profitability has a positive and significant effect on the Earning Response Coefficient. Meanwhile, simultaneously Firm Size, Leverage, and Profitability have a positive effect on Islamic Social Reporting. Simultaneously Firm Size, Leverage, Profitability and Islamic Social Reporting on Earning Response Coefficient. Based on the results of path analysis, it shows that Islamic Social Reporting cannot mediate Firm Size, Leverage, and Profitability variables on the Earning Response Coefficient.